Dibenzo[b,f][1,5]Diazocines/ZnO Organic/Inorganic Hybrid Photoanodes for Efficient Photo Electrochemical Water Splitting - Sissembayeva Yana; Soo Kyung Cho; Yoon-Hwae Hwang (International Journal of Photoenergy)
In this study, we propose dibenzo[b,f][1,5]diazocine/ZnO organic/inorganic hybrid photoanode for application in the photoelectrochemical water splitting. The electrode consisting of inorganic ZnO nanorod (ZnO NR) array structures and organic diazocine derivative film with or without platinum nanoparticle (Pt NP) cocatalyst was examined. The morphology characterization was performed by FESEM. UV-vis absorbance spectra showed enhanced absorbance in the visible light spectrum for the hybrid sample. Photoluminescence analysis of a hybrid sample showed a significant decrease in charge recombination and enhanced charge separation. Photoelectrochemical measurements revealed an increase in current density for the organic/inorganic hybrid photoanode reaching 1.256 mA/cm2 at 1.23 V vs. RHE which is almost two times higher than bare ZnO NR arrays (0.716 mA/cm2 at 1.23 V vs. RHE). The addition of the Pt NP cocatalyst further enhanced the photocurrent density up to 1.636 mA/cm2. Therefore, proposed organic/inorganic hybrid photoelectrode is a promising candidate for the efficient solar water splitting.